COMPARATIVE ANALYSIS OF ABILITY AND THE WILLINGNESS TO PAY THE COMMUNITY WITH UNIT COST (Case Study of Inpatient Mental Hospital in Maluku Province) - Fajrin, Muhamamd Al; Darmawansyah,; Syafar, Muhammad; Arifin, Muhammad Alwy; Razak, Amran; Saleh, Lalu Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Rational tariff determination is done by calculating unit costs and also considers the ability and willingness to pay the community. This study aims to determine the comparison of tariffs that are calculated based on the level of ability and willingness to pay the community with unit costs. This research is quantitative research with a descriptive survey. The population in this study were all general patients undergoing inpatient treatment at the Maluku Province Special Hospital in 2019 as many as 512 people. The sample in this study was general patients undergoing inpatient care. the number of samples obtained by using accidental sampling technique was 45 people. The results of the study showed that the tariff based on unit cost was IDR. 497,732, above ATP IDR. 453,667, and WTP IDR. 429,444, for Class 1 tariffs based on unit costs of Rp. 260,571, - above ATP Rp234,818, and WTP IDR204,545, for class 2 tariffs based on unit costs of IDR. 186,675, - above ATP IDR. 182,100 and WTP IDR160,500 and class 3 tariffs IDR138,093, and still above the ATP IDR. 134,040 and WTP IDR. 134,000. Hospitals can make rational tariff revisions taking into account unit costs and ability and willingness to pay